Incidence of Income Taxation in Sri Lanka. - Vijayakumaran, R.; Vijayakumaran, S. (Research Journal of Finance and Accounting, 2014)
Taxation is a major instrument of fiscal policy which is used to achieve socio economic objectives. While the primary objective of taxation is to raise revenue to finance government expenditure, it should also be equitable. This study aims to identify the nature of distribution of income tax burden among the income groups in Sri Lanka and provides taxpayers and policymakers with important information on the equity or fairness of the income tax distribution in Sri Lanka. In the case of personal income taxes the burden is unevenly distributed among the registered taxpayers. The study finds that about 87.93 percent of resident individual income taxes shared by only 10.9 percent taxpayers. About 32.95 percent taxpayers pay almost 98.5 percent of income taxes. It depicts the peculiarity of Sri Lanka tax structure where about 43.76 percent of registered individual taxpayers share very insignificant (only 0.97 percent) tax liability. In the case of corporate taxes the major portion of the tax revenue is generated from a small group of companies and corporations. About 66.77 per cent corporate tax payers are paying no taxes for the government showing negative income and revealed as loss cases. About 99 per cent of income tax burden is placed on a small number of (about 13 per cent) corporate tax payers. This study also gives some recommendations which act as remedies for a better tax system in Sri Lanka and would be relevant to other developing countries as well.
Keywords: Equity of taxation; Economic Incidence; Income tax; Statutory Incidence